2008
DOI: 10.3382/ps.2008-00119
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Maternal Antibody Transfer to a Group of Pathogens in Meat-Type Chickens

Abstract: This study was conducted to evaluate the rate of antibody transfer on a flock basis from hens to their day-old chicks in meat-type chickens raised in a commercial setting. Fifteen randomly selected hens from a commercial broiler-breeder flock were bled at 37, 40, and 45 wk of age. At day of bleeding, the collected eggs were identified and tracked through hatching where 30 hatchlings were randomly sampled and bled from the jugular vein. Antibodies against 10 different pathogens were quantified from the collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 22 publications
1
25
0
7
Order By: Relevance
“…The transfer of immunoglobulin/antibodies to the offspring has been reported in diversified vertebrates such as avian [92], mammal [6], reptile [93] and fish [94][95][96][97][98][99][100][101][102][103][104][105][106][107]. Successful transfer of maternal IgM to eggs and embryos has been documented in several teleostean fishes like plaice (Pleuronectes platessa), tilapia (Oreochromis aureus), carp (C. carpio, Labeo rohita), sea bream (Sparus aurata), sea bass (Dicentrarchus labrax), and rainbow trout (O. mykiss) [109][110][111] ( Table 2).…”
Section: Immunoglobulins/antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of immunoglobulin/antibodies to the offspring has been reported in diversified vertebrates such as avian [92], mammal [6], reptile [93] and fish [94][95][96][97][98][99][100][101][102][103][104][105][106][107]. Successful transfer of maternal IgM to eggs and embryos has been documented in several teleostean fishes like plaice (Pleuronectes platessa), tilapia (Oreochromis aureus), carp (C. carpio, Labeo rohita), sea bream (Sparus aurata), sea bass (Dicentrarchus labrax), and rainbow trout (O. mykiss) [109][110][111] ( Table 2).…”
Section: Immunoglobulins/antibodiesmentioning
confidence: 99%
“…Swain, S.K. Nayak / Fish & Shellfish Immunology27 (2009) [89][90][91][92][93][94][95][96][97][98][99] …”
mentioning
confidence: 99%
“…This protein presents similar characteristics as some poxviruses and the murine gamma herpesvirus 68 (MHV-98), and their function is to evade host immune responses (Coppo et al, 2013b). Maternal antibodies are transmitted to offspring via eggs (Benton et al, 1960), as shown by their presence in day-old chicks (Gharaibeh et al, 2008); however, they do not protect against infection or interfere with vaccination (Fahey et al, 1983).…”
Section: Immune Response To Iltvmentioning
confidence: 99%
“…Previous results from our laboratory estimated the rate of mAb transfer from the parent flock to their chicks (Gharaibeh et al, 2008). This study was designed to estimate the half-life of these mAb against different pathogens in broiler chicks.…”
Section: Introductionmentioning
confidence: 99%